(untitled) (Journal of the College of Basic Education, 2023)
Is a technical skill in drawing and learned the lesson of Art Education, one supplies the task to be met by the students of the intermediate stage, to adopt the rest of the subjects in the implementation of the requirements of illustrations, especially biology, so the appraisal that skill , and detection level of the students and the statement of the positive aspects and negative acquires its importance from the importance and contribute to the improvement and calendar it.